THE EFFECT OF MOTHER'S KNOWLEDGE ON WASTING INCIDENTS IN TODDLER - Anggita Septyani Permatasari; Rosmala Kurnia Dewi (LPPM AN NUUR, 2024)
Background: Wasting is an acute malnutrition condition where body weight does not correspond to height and the z-score is < -2. Wasting often occurs in poor and developing countries and requires serious treatment. Purposes: This study aims to analyze the influence of maternal knowledge on the incidence of wasting in toddlers. Method: This research uses quantitative methods. The design of this research is an observational study with a cross-sectional design. The sampling technique uses purposive sampling. Data analysis used the Chi Square test. Results: using the chi square test, it was found that the knowledge of mothers of toddlers regarding the incidence of wasting (p value 0.000). Conclusion: There is an influence of the knowledge of mothers of toddlers on wasting incidents at PMB Sri Lestari.